Pengetahuan, Sikap dan Perilaku Ibu Rumah Tangga dalam Pencegahan Penyakit Demam Berdarah Dengue - Thia Prameswarie; Indri Ramayanti; Ghina Zalmih (Sarana Ilmu Indonesia (salnesia), 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus that can be transmitted through mosquitoes, therefore, the role of housewives in efforts to eradicate mosquito nests in the home environment is critical. The purpose of this study was to determine the relationship between housewives' knowledge, attitudes, and behavior in preventing dengue fever in Beti Village, South Indralaya District, Ogan Ilir Regency. The study was observational analytic in nature, with a cross-sectional design. Simple random sampling was used as the sampling technique, with 49 subjects. Questionnaires and interviews were used to collect data. The analysis was carried out using univariate and bivariate analysis, as well as the chi-square test. According to the univariate analysis, 71,4 percent of the subjects had poor knowledge, 75,5 percent disagreed, and 79,6 percent exhibited negative behavior. In Beti Village, South Indralaya District, Ogan Ilir Regency, there is a significant relationship between knowledge (p- value = 0,004), attitude (p-value = 0,001), and behavior (p-value = 0,004) in preventing DHF. According to the findings of this study, the community already has a fairly good level of knowledge and attitude toward DHF prevention, but behavior in terms of preventing DHF still needs to be improved.